Halal Maritime Industry and the Blue Economy: Integrating Legal and Fatwa-Based Strategies for Sectoral Transformation - Rachman, Abdul; Lukman Santoso; Imamuddin, Imamuddin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
This study examines the repositioning strategies of Indonesia’s halal maritime industry within the framework of the blue economy, employing positive law and fatwas issued by the Indonesian Ulama Council (MUI). Despite Indonesia’s considerable maritime potential, the halal maritime sector remains underdeveloped, thereby necessitating strategic repositioning. Utilizing a qualitative, descriptive-analytical, and normative juridical methodology, the research reveals that the proposed strategies correspond with Elkington’s Triple Bottom Line Theory across five key pillars: (1) cross-sectoral regulatory harmonization that integrates public policy, legislation, and halal fatwas; (2) development of halal maritime infrastructure, encompassing ports, cold chain logistics, transportation, certification processes, and blockchain-based traceability; (3) institutional collaboration among government agencies, BPJPH, BPOM, and MUI concerning derivative products; (4) establishment of a comprehensive halal maritime ecosystem; and (5) enhancement of halal seafood export competitiveness to support halal diplomacy. The study contributes theoretically by bridging the blue economy concept with legal frameworks and fatwas, and offers a practical, sustainable model for industry repositioning. Policy implications underscore that, without the integration of regulatory measures and fatwas, the halal maritime industry will remain marginal and fail to serve as a catalyst for Indonesia’s Islamic economic development.